THE CORRELATION BETWEEN SMOKING ADDICTION LEVELS AND OXYGEN SATURATION VALUES DURING INTRAOPERATIVE GENERAL ANESTHESIA IN LAPAROTOMY SURGERY AT RSUD 45 KUNINGAN - Rully Annisa; Harley Thaariq Alath Thuur (Journal of Indonesian Anesthesiology Nursing, 2024)
Background: Patients undergoing general anesthesia are a trisk of experiencing disturbances in respiration, circulation, and hemodynamics. Oxygen binds with hemoglobin to facilitate perfusion throughout the body. Smoking habits lead to the accumulation of toxic substances in the body and are a factor affecting oxygen saturation in the blood stream. This is influenced by changes in hemoglobin levels, poor blood flow, and mucus secretion accumulation in the respiratory tract due to hypersecretion of mucus. To investigate the relationship between smoking addiction levels and oxygen saturation values during intra operative general anesthesia in laparotomy surgery at RSUD (Regional Public Hospital) 45 Kuningan.  Methods: A quantitative study with a cross-sectional design. The sample consisted of 55 patients undergoing laparotomy with general anesthesia, selected through purposive sampling. Data analysis was performed using Spearman's rank correlation test.  Results: A significant relationship was found (p-value=0.000) between smoking addiction levels and oxygen saturation values in patients undergoing laparotomy with general anesthesia, with a correlation coefficient of -0.726.  Conclusion: There is a correlation between smoking addiction levels and oxygen saturation values during intra operative general anesthesia in laparotomy surgery at RSUD 45 Kuningan.